(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2015)
This research aimed to explain the improvement of students’ vocabulary of the noun (abstract noun and concrete noun), Verb (regular verb and irregular verb) and adjective (Descriptive adjective).The method of this research was classroom action research consisted of two cycles. One cycle consists of four meeting. Thus there were eight meetings for two cycles. This classroom action research was done at the second year of SMA Negeri 1 Enrekang. As the subject of this research was class XI in 2011/2012 academic year with students’ number about 31 students. These consist of 23 women and 8 men. The instruments of this research were observation sheet and vocabulary test or evaluation. The findings of the research were the students’ score in vocabulary mastery through the bilingual magazine. Before applying this media in teaching and learning vocabulary, the students’ mean score in D-test was 4.6 (poor). After applying bilingual magazine as a media of teaching and learning process, in cycle I the students’ mean score improved to 5.35(fair) and then in cycle II also improved to 7.20 (fairly good).